Oral skills and Flipgrid platform in english as a foreign language learners - Fajardo-Guapisaca, Mercy Marlene; Argudo-Garzón, Antonio Lenín (Revista Arbitrada Interdisciplinaria Koinonía, 2022)
Speech has often been the main problem when students learn a second language. Therefore, the main objective of this study was to analyze how to improve interactive communication and pronunciation by using the Flipgrid platform with A1 level students at the Salesian Polytechnic University. For this purpose, a Diagnostic Test, a Cambridge Speaking test and a guided response survey were applied. The research collected data to assess the effect of the Flipgrid platform on students' speaking skills and to learn about students' perceptions towards the Flipgrid platform. The results provided information on students' failures in speaking, the benefits of the Flipgrid platform, and a proposal with recommendations for using this platform with A1-level university students.